Mediated space the architecture of news, advertising and entertainment - Brown, James Benedict (RIBA Publishing, 2018)
Organised into three parts - the mediated space of broadcast news, advertising and entertainment - the book explores the interface between space, broadcast media and architecture, offering a compelling critique of how these elements collude to assert a particular message or power structure. Academic in rigour, but accessible in tone and intent, Mediated space will challenge ways of seeing and knowing, (showing how these are co-produced by the creators and consummers of space), raising as many questions as it answers.-- from back cover
Description based on print version record
Keywords: Architecture and technology; Media architecture; Architecture and society; Architecture / Psychological aspects; Digital media; Broadcasting; Advertising; Television